2022
DOI: 10.3390/mca27020021
|View full text |Cite
|
Sign up to set email alerts
|

Attention Measurement of an Autism Spectrum Disorder User Using EEG Signals: A Case Study

Abstract: Autism Spectrum Disorder (ASD) is a neurodevelopmental life condition characterized by problems with social interaction, low verbal and non-verbal communication skills, and repetitive and restricted behavior. People with ASD usually have variable attention levels because they have hypersensitivity and large amounts of environmental information are a problem for them. Attention is a process that occurs at the cognitive level and allows us to orient ourselves towards relevant stimuli, ignoring those that are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Sensitivity, also known as Recall [84], measures the proportion of positives that are correctly identified as such; it can be calculated by (9). Similarly, Speci f icity measures the proportion of negatives that are correctly identified as such [84]; it can be calculated by (10). Precision is the proportion of true positives among the positive predictions [84]; it can be calculated by (11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity, also known as Recall [84], measures the proportion of positives that are correctly identified as such; it can be calculated by (9). Similarly, Speci f icity measures the proportion of negatives that are correctly identified as such [84]; it can be calculated by (10). Precision is the proportion of true positives among the positive predictions [84]; it can be calculated by (11).…”
Section: Resultsmentioning
confidence: 99%
“…Electroencephalography (EEG) is a non-invasive procedure for measuring the electrical activity generated within the brain as a result of different mental processes [10]. The electrical signals are acquired through electrodes placed on the scalp's surface; thus, waves with different amplitudes and frequencies that refer to a person's mental state are obtained [11].…”
Section: Introductionmentioning
confidence: 99%
“…Data is filtered and the output is a 256 Hz clean signal in the 0.2-45 Hz range [10]. A number of studies showed that this EEG headset was effective in acquiring research-grade data for studying attention, auditory event-related potentials, neurofeedback games for enhancing attention and memory, and inter-brain synchrony in teams across different settings, learners, and tasks [11][12][13][14].…”
Section: Eeg Data Acquisition and Processingmentioning
confidence: 99%
“…Recent research has focused on examining how human and machine behavior interact, acknowledging that differing social and psychological origins might affect various forms of human-computer interaction [26]. Techniques for extracting EEG features have repeatedly been shown to be clinically reliable in evaluating and diagnosing a range of cognitive and neurological domains in conditions such as ASD [27][28][29][30], learning difficulties [31], and attention-related issues [32][33][34][35]. It is commonly acknowledged that artificial intelligence (AI) tools can be used to automatically diagnose and treat ASD cases.…”
Section: Introduction and Related Workmentioning
confidence: 99%